2009
DOI: 10.3144/expresspolymlett.2009.21
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and photopolymerization of vinyl functionalized poly (ε-caprolactone)

Abstract: Abstract. Vinyl functionalized poly (ε-caprolactone) with molar mass ranging from 500-5000 Da were synthesized by ring opening polymerization and further photopolymerized. One-step synthesis and functionalization is achieved based on ring opening polymerization (ROP). Hydroxyl butyl vinyl ether (HBVE) was employed to play the role as the initiator of ROP, and photo-curable functional group. The presence of CH2=CH peak in Fourier Transform Infrared (FTIR) spectra confirmed that vinyl end groups were successfull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Targeted soft segment molar mass was achieved by controlling the total monomer/initiator ratio [21][22][23]. The mechanism of the cyclic esters ROP at the presence of Sn(Oct) 2 as catalyst was proposed in several studies [24,25].…”
Section: Results and Discussion 31 Polyurethanes Synthesis And Charmentioning
confidence: 99%
“…Targeted soft segment molar mass was achieved by controlling the total monomer/initiator ratio [21][22][23]. The mechanism of the cyclic esters ROP at the presence of Sn(Oct) 2 as catalyst was proposed in several studies [24,25].…”
Section: Results and Discussion 31 Polyurethanes Synthesis And Charmentioning
confidence: 99%
“…A Sn‐free catalyst based on Al has been used in the polymerization of ɛ‐CL at room temperature, similarly to the procedure described by Liow et al . (), with the modification of the initiator used. Here HEVE has been used as photocurable initiator (Liow et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…E a was calculated to be 14 kJ/mol. From previous study [9], VPCL showed E a of 11.3 kJ/mol. In other words, VPCL was slightly more reactive than VPCLA.…”
Section: Uv Curing Kinetics Studies Of V/a Oligo-caprolactonementioning
confidence: 96%
“…Cationic photopolymerization is capable of dark curing and it is insensitive to oxygen and impurities inhibition, which are critical towards complete conversion. In earlier work, we reported the kinetics studies of the VE monofunctionalized-caprolactone oligomers (VPCL) [9]. The monofunctional system was photopolymerized readily via cationic mechanisms, with 97% conversions.…”
Section: Introductionmentioning
confidence: 99%